Simultaneous Visible and Near-Infrared Variability of Classical T Tauri Stars. Issue Volume 8:Issue S299(2013) (6th January 2014) - Aimi, Yukako; Fukagawa, Misato; Yasuda, Tomonori; Yamashita, Takuya; Kawabata, Kouji; Uemura, Makoto; Arai, Akira; Sasada, Mahito; Ohsugi, Takashi; Yoshida, Michitoshi; Shibai, Hiroshi
Abstract: Temporal structural changes of protoplanetary disks surrounding T Tauri stars (TTSs) can cause magnitude variations of TTSs. On the other hand, variability is also expected due to cool spots and/or hot spots on the surface of the star, thus it is important to distinguish the causes of the observed variability. Our sample consists of 23 TTSs (22 classical T Tauri stars, 1 weak-lined T Tauri star) and 4 Herbig Ae/Be stars. The observations were performed over a period of about 3 months in the V, J, and K S band, simultaneously. We detected variability for all stars in the three bands (>0.05 mag in V, >0.09 mag in J, >0.09 mag in K S ). Color-magnitude relations obtained between V, J, and K S bands suggest that stellar spots are not the only cause of variability for most of our targets. In addition, the data implies that six stellar systems contain larger grains than in the interstellar medium if the variability is only caused by extinction due to circumstellar matter.